(untitled) (Agro Productividad, 2024)
The essential oils of aromatic and medicinal plants are an important resource used to control several health conditions; however, information about their composition and antimicrobial activity is scarce. This study used a gas chromatography-mass spectrometry (GC-MS) to analyze the composition of the essential oil (EO) of Tagetes lunulata Ort., a Mexican endemic plant, known as wild cempaxúchitl. The major components of the EO include: verbenone (47.17%), α-pinene (10.93%), 1,1,1-Trifluoro-2-hexanone (9.63%), β-caryophyllene (6.10%), germacrene-D (4.99%), L-verbenone (4.89%), and E-tagetone (4.44%). The disk agar diffusion method was used to evaluate the antimicrobial activity of T. lunulata against Trichophyton rubrum (athlete’s foot). A significant antimicrobial activity was observed with a ≥60% EO concentration. The dilution method was used to determine the minimum inhibitory concentration (MIC): 200 μg ml-1. The T. lunulata EO recorded a strong antimicrobial activity against T. rubrum; therefore, it is a natural alternative for the control of natural antifungals.